Modeling and experimental study of machining outcomes when conducting nanoscratching using dual-tip probe on single-crystal copper. (15th September 2021) - Geng, Yanquan; Jia, Junshuai; Li, Zihan; Liu, Yu; Wang, Jiqiang; Yan, Yongda; Gan, Yang
Highlight: A depth prediction model is developed for the nanoscratching process using the dual-tip probe. The symmetrical three-dimensional nanostructures composed of two large pile-ups and one small hump can be machined successfully with the dual-tip probe. The ratio of the intermediate hump height to the machined depth decreases as the applied normal load increases. The proposed model predicts the machined nanostructure depth accurately when the machined depth reaches approximately 40 nm. The molecular dynamics simulation results agree well with the experimental outcomes for the nanoscratching process with the dual-tip probe. Abstract: Atomic force microscopy (AFM) tip-based nanomachining technique has been proved as a powerful method to fabricate nanostructures. The nanomachining approach proposed in this study offers a new concept to improve the width resolution and processing efficiency of AFM tip-based nanofabrication techniques. The method uses a dual-tip probe and single-crystal copper is used as the sample material. A depth prediction model is developed for the nanoscratching process using the dual-tip probe. The results obtained by nanoscratching tests show that symmetrical three-dimensional (3D) nanostructures composed of two large pile-ups and one small hump can be machined. The model predicts the machined nanostructure depth accurately when the machined depth reaches approximately 40 nm; the blunt tip and the inclined inner wall of the dual-tip gap may be the main reasons for the inaccurate predictions at smaller machined depths. Moreover, molecular dynamics (MD) simulation is also used to investigate the scratching process with the dual-tip probe. The simulation results obtained agree well with the experimental results. Graphical abstract: Image, graphical abstract